EFEKTIVITAS MEMBACA DAN MENTADABBURI AL-QUR’AN DALAM MENURUNKAN KECEMASAN SISWA YANG AKAN MENGHADAPI UJIAN SEKOLAH - Eri Yudhani; Veni Suharti; Annisa Adya; Eliza Sutri Utami (State Islamic University (UIN) Ar-Raniry, 2017)
This study aimed to reduce student’s anxiety through reading and tadabbur al-Qur’an. Research used an experimental method with pretest-posttest control group design. Each experimental group and control group consisted of 5 3rd grade students of senior high school, who able to recite reading Qur’an. To measure student’s anxiety was used Fadlillah’s scale (2011). The results showed differences in student’s anxiety in experimental group and control group, p = 0,045 (p < 0,05). This study showed that reading and tadabbur Qur’an could reduce student’s anxiety. Weaknesses and the implications of this research are also discussed in this paper.